Yeh-Shen : a Cinderella story from China - Louie, Ai-Ling (Philomel Books, 1982)
This version of the Cinderella story, in which a young girl overcomes the wickedness of her stepsister and stepmother to become the bride of a prince, is based on ancient Chinese manuscripts written 1000 years before the earliest European version.